Agricultura familiar e políticas públicas: estudo sobre o Banco da Terra no município de Canguçu, RS - Silva, Fernanda Novo da (2009)
This dissertation analyzes the process of implementation of the program of agrarian credit Bank of the Land (Banco da Terra) in the city of Canguçu - RS, centering the inquiry in the examination of the conditions of social and economic reproduction of its beneficiaries, after the grace period of three or more years. The emphasis was equally put on the analysis of the capacity of the beneficiaries in honoring its contractual commitments with the financial agent, as well as in the direction of pointing what evaluation these families make regarding the program, considering their future perspectives. The present work of inquiry counted on the application of 62 questionnaires on families who had acquired their country properties between the years of 2000 and 2001 as well as interviews carried through with diverse social actors connected to the process of implementation and conduction of the program in the regional and local scope. The data of the research disclose that in general terms the insolvency reaches 12.9% of contracts. However, calls attention the fact that in such elapsing of time there was an increase of the tax of payments as result of the process of renegotiations taken by the financial agent. However, there is a recurrent aspect between the families: the ones that had honored and the ones that had not honored the schedule of the parcels reflect a picture of innumerable difficulties that they had been submitted to in the period following the installation in the land, especially in terms of administrative and technique assistance. On the other hand it was demonstrated that among the defaulters there is a great ratio of former-dayworkers, people who knowingly did not congregate professional experience compatible with the necessity to manage their proper business. The research evidenced that most of the beneficiaries (91.9%) evaluates positively the choice of this acess way to the land and 98.4% of the families consider their current situation as sufficiently positive, in analogy to the situation before the acquisition of the land.